The Caged Soul of Billy A case of Gender Dysphoria: The Journey of Billy: Overcoming Gender Dysphoria and Embracing Identity (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Gender Identity Disorder (GID) is a complex psychological problem. According to American Psychiatric Association (APA) Gender Dysphoria involves a conflict between a person physical or assigned gender and the gender with which he, she, they identify themselves. People with Gender Identity Disorder or Gender Dysphoria may be very uncomfortable with the gender they were biologically assigned with, sometimes described as being uncomfortable with the expected role with their assigned gender. People with GID may often experience significant distress andor problem associated with this conflict between the way they feel and think of themselves and their physical or assigned gender. This basically includes class of Lesbians, Gays, Bisexual, and Transgender or Transsexuals (LGBT). These people are individuals of any age or sex whose appearance, personal characteristics’, or behaviors differ from stereotypes regarding how men and women are “supposed” to be. The case discusses GID as a disorder, its diagnosis, line of treatment and coping methods with its implication on socio-economic frameworks. Billy who suffered from GID and struggled hard each day in search of his real identity. In spite of the being dejected from the society, he stood against the unwritten norms of stereotyped world. Right from the beginning till the end of his problem he fought bravely keeping aside the traumas that he had gone through right from parent’s separation to sexual assault, lost days of childhood, social boycott and pain related to gender transformation etc. He stood again all odds and created a new identity(by undergoing sexual transmission process).This is how he made a choice and took a brave a decision of placing his soul in the right body and won the major battle of life. His caged female soul was freed from the body of a male. He did so by altering his gender from male to a female.